Controllable morphology of Pd-loaded potassium tantalates with high catalytic performance for ethylene glycol electrooxidation. (20th April 2021) - Zheng, Xiaoguang; Wang, Gen; Zhao, Yanhong; Wu, Liyuan; Wang, Yuanjiang; Song, Yanyong; Tian, Peijun; Wang, Xiaojing
Highlights: The octahedral pyrochlore K2 Ta2 O6 and cubic perovskite KTaO3 were synthesized successfully. The Pd nanoparticles were loaded onto the Kx Tax O3x ( x = 1 or 2) by a reflux method. Pd loading enhanced the electron transfer between Pd and Kx Tax O3x . The Pd/Kx Tax O3x electrocatalysts exhibited excellent electrocatalytic activity for EG oxidation. The electrocatalytic activity of Pd/Kx Tax O3x was superior to that of commercial Pd/C (10%). Abstract: In this work, potassium tantalates (Kx Tax O3x, x = 1 or 2) with different crystal structures and morphologies are synthesized with a one-step hydrothermal method. The concentration of the KOH reactant played a crucial role in controlling the morphology of Kx Tax O3x . When the concentration of KOH is low, an octahedral pyrochlore (K2 Ta2 O6 ) is obtained. In contrast, the cubic perovskite (KTaO3 ) is obtained at high KOH concentrations. Pd nanoparticles loaded onto K2 Ta2 O6 and KTaO3 (Pd/K2 Ta2 O6, Pd/KTaO3 ) electrocatalysts are then prepared with reflux reduction in ethanol. X-ray photoelectron spectroscopy results imply that the loading palladium is in the main Pd° form. The electrocatalytic activity of the Pd/K2 Ta2 O6 and Pd/KTaO3 electrocatalysts is investigated using cyclic voltammetry (CV) toward ethylene glycol (EG) oxidation in an alkaline medium. The CV results show that Pd/K2 Ta2 O6 and Pd/KTaO3 electrocatalysts modified glassy carbon electrodes have excellent catalytic activity for EG electrooxidation in an alkaline medium, superior to that of commercial Pd/C (10%). The enhancement of their electrocatalytic activity was owing to the synergistic reaction between Pd and Kx Tax O3x . In addition, the electronic structure of the Pd/K2 Ta2 O6 and Pd/KTaO3 electrocatalysts was assessed using density functional theory. The calculation results indicated that electron transfer occurred in the complex region of Pd and Kx Tax O3x . Graphical abstract: Image, graphical abstract